The Effect of Sulphurous Humic Acid and Plant Density on the Growth and Yield of Red Beans (Phaseolus vulgaris L.) Cultivars - Zeinab Jabbari Badkhor; Alireza Dadkhah; Reza Rezvani (پژوهش‌های حبوبات ایران)
IntroductionPulses, including red beans, are a significant source of protein in human nutrition. Increasing yield per unit area is one of the most important factors for increasing crop production. Todays the increase in crop yield occurred by the excessive use of chemical fertilizers, including nitrogen fertilizers, which caused environmental hazards and consequently human health. Humic acid is a natural organic polymer compound that results from the decay of soil organic matter, peat, lignin, etc., which can be used to increase the product and its quality. One of the important benefits of using humic acid is the ability to chelate various nutrients such as potassium and magnesium and other elements to overcome the lack of nutrients. Humic acid also creates more space for water to penetrate through physical modification and improved soil granulation. Plant density is another important agronomic factor that manipulates micro- environment and affects growth, development and yield of plants. Within certain limits, increase of plant population density declines the growth and yield per plant but the reverse occurs for yield per unit area. The optimum plant density to attain highest yield may vary with the genotype and agronomic factor. Therefore, the purpose of this research was to investigate the effect of sulphurous humic acid and plant density on growth and yield of red beans (Phaseolus vulgaris L.) cultivars (Ofogh, Dadfar and Yaghoot). Materials and MethodsThe experiment was conducted as a factorial based on a randomized complete blocks design with three replications in the Bojnord city located in north east of Iran during the year 2022. The experimental factors were: plant density at three levels (18, 25, and 40 plants per m2, sulfur-containing humic acid (0 (no application humic acid) 4 and 6 liters per hectare) and red bean (Phaseolus vulgaris L.) cultivars (Ofogh, Dadfar and Yaghoot). Humic acid treatments were applied in the stages of two to four leaves, before flowering and after pod formation, depending on the level of treatment. Results and DiscussionThe results showed that Yaghoot cultivar had the highest plant height (71 cm) while, Dadfar had the lowest plant height (40 cm) at all three plant densities. Yaghoot cultivar also had the highest seed number per pod (4.1) and seed yield (4450 kg.ha-1) with application of 6L per hectare humic acid while, Dadfar cultivar had the lowest seed per pot (2) and seed yield (766 kg.hac-1). Results showed the best cultivar was Yaghoot and then Ofogh due to growth traits. The best plant density was 40 plants per m2 and among the humic acid levels, application of 6 lit per hectare had the best results. In the absence of fertilization, the amount of total chlorophyll of cultivars Yaghoot and Ofogh was not affected by the density, However, increasing of humic acid significantly increased the amount of total chlorophyll in all three cultivars and the highest amount of chlorophyll obtained at the highest level of humic acid and plant densities 18 and 25 for Yaghoot and the density of 18 plants for Dadfar.  ConclusionsIn general, it was concluded that humic acid and plant density have been able to have a positive effect on most of the growth traits and photosynthetic pigments of red bean plant. The best cultivar was Yaghoot variety and then Ofogh variety and the best plant density was 40 plants per square meter. Among the humic acid levels, the consumption of 6 liters per hectare had the best result. By observing the appropriate level of density, variety and humic acid, we will be able to harvest the maximum yield of red bean (Phaseolus vulgaris L.) cultivars (Ofogh, Dadfar and Yaghoot) in Bojnord region.